State-building through neotrusteeship: Kosovo and East Timor in comparative perspective - Lise Morjé Howard (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Why do some states, with foreign assistance, transition from 'fragile' to 'robust?' Scholars in state-building have argued that neotrusteeship is an effective strategy by which external organizations might build post-conflict states. This working paper tests this hypothesis, and two related propositions, in a paired comparison between Kosovo and East Timor. The two states are ideal for comparison in that they share many similar characteristics, including, most crucially, the fact that both experienced regional peace enforcement operations to end violent conflict, followed by massive neotrusteeship operations. However, they have had divergent results in post-conflict state-building: While the state and economy are gradually becoming stronger in East Timor, the same cannot be said of Kosovo, which continues to be plagued by high unemployment, low growth, corruption, and organized crime. Many of Kosovo's problems can be traced back to the strategy of dividing international responsibility for the neotrusteeship operations.
Keywords: O19; F5; 330; Kosovo; East Timor; United Nations; peacekeeping; neotrusteehsip; post-conflict development